Equity Issues and Changes in Expectations of Earnings by Financial Analysts - Jain, Prem C. (Review of Financial Studies, 1992)
Evidence is provided on an implication of models by Myers and Majluf (1984) and Miller and Rock (1985), which predict that equity issues convey information about firms' future earnings. Consistent with the prediction, the results show that earnings forecast revisions by financial analysts subsequent to the announcement of equity issues are significantly related to announcement period abnormal returns. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.